(3OhQ GdefXeGJ GdMbhbjI aj Jecjf GdeQCI GdeUQjI (B: s (3OQGSI MGdI GdeQcR GdeUQj dMbhb GdeQCI (B2011-2021 /s - (3,fQejf YdGA GdOjf eMeO MSf Ydj fVQs; (3eUWai cGed GdSjOs (2024)
(3jJeKd GdESgGe GdQFjS dgPg GdOQGSI aj JMdjd OhQ GdeQcR GdeUQj dMbhb GdeQCI aj JYRjR Jecjf GdfSGA SjGSjkG hGbJUGOjkG, hJbjje aYGdjI GSJQGJjLjGJg hHQGeLg aj JMbjb gPG GdJecjf(B. (3bO SYJ GdOQGSI Edi GdELGHI Ydi GdJSGDd GdHMKj GdQFjS Mhd SHH JYKQ Jecjf GdeQCI GdeUQjI SjGSjkG hGbJUGOjkG Ydi GdQZe ef eTGQcI GdeQCI HOhQ gGe aj KhQI (B25 (3jfGjQ (B2011 (3heWGdHJgf HGdJecjf, hYdi GdQZe ef LghO GdefXeGJ GdMbhbjI HTcd YGe hGdeQcR GdeUQj dMbhb GdeQCI HTcd NGU(B. (3hGSJNOeJ GdOQGSI efgL CSdhH OQGSI GdMGdI hefgL JMdjd GdfXe ddJYQa Ydi GdYhGed GdeDKQI aj aYGdjI HQGeL Jecjf GdeQCI GdJj jfaPgG GdeQcR GdeUQj dMbhb GdeQCI, hJMdjd eOi JCKjQ gPg GdHQGeL hGdOhQGJ Ydi hGbY GdfSGA GdeSJajOGJ(B. (3hbGeJ GdHGMKI HOQGSI ejOGfjI eY GdfSGA GdeSJajOGJ ef GdeQcR GdeUQj hELQGA ebGHdGJ eY GdSGOI GdeOQGA GdeSDhdjf Yf GdeQcR, hPdc dGSJWdGY GdBQGA Mhd aYGdjI GdHQGeL hGdOhQGJ GdoebOeI(B. (3NdUJ GdOQGSI Edi YOO ef GdfJGFL, efgG JCKjQ HQGeL hOhQGJ GdeQcR Ydi GdfSGA GdeSJajOGJ heOi JMbjbgG ddCgOGa GdeQLhI(B. (3heY Pdc, CXgQJ GdOQGSI hLhO aLhGJ aj JfajP gPg GdHQGeL hGdOhQGJ, HGdEVGaI Edi JMOjGJ JYjb JMbjb fJGFL aqYGdI aj Jecjf GdfSGA, QZe GdLghO GdeHPhdI ef bHd GdeQcR(B. s
The main contribution of this study lies in analyzing the role of the Egyptian Center for Women's Rights in promoting the political and economic empowerment of women, and assessing the effectiveness of its strategies and programs in achieving this empowerment. The study sought to answer the main research question regarding why the political and economic empowerment of Egyptian women has faced challenges despite their significant role in the January 25, 2011 revolution and their calls for empowerment, as well as the efforts of women$1 (Bs rights organizations in general, and the Egyptian Center for Women's Rights in particular. The study employed a case study approach and systems analysis methodology to identify the factors influencing the effectiveness of the women$1 (Bs empowerment programs implemented by the Egyptian Center for Women's Rights, and to analyze the impact of these programs on the actual lives of the women beneficiaries. The researcher conducted a field study with the beneficiaries of the center and held interviews with the responsible managers at the center to gather opinions on the effectiveness of the programs offered. The study concluded with several findings, including the impact of the center's programs and courses on the beneficiaries and the extent to which they achieved the desired goals. However, the study also revealed gaps in the implementation of these programs and courses, as well as challenges hindering the achievement of effective results in empowering women, despite the center's efforts. Additionally, the study highlighted the need for the development of more appropriate and inclusive strategies that better reflect the needs of the beneficiaries, and to enhance collaboration with various stakeholders in order to achieve empowerment goals more efficiently.s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B203-227.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdeQCI GdeUQjIs; (3GdeQCI s -- (3GdGMhGd GdSjGSjIs; (3GdJecjf GdSjGSjs -- (3GdJecjf GdGbJUGOjs -- (3Jecjf GdeQCI GdeUQjIs